Are teams whose players are more committed to the team more resilient? The role of intra-group conflict - López-Gajardo, M. A.; García-Calvo, T.; González-Ponce, I.; Cantú-Berrueto, A.; Parma-Aragón, M.; Moncada-Jiménez, J.; Salicetti-Fonseca, A.; Tassi, J. M.; Leo, F. M. (Journal of Human Kinetics, 2022)
The study aimed to analyze the relationship between commitment to the team and team resilience factors (characteristics of resilience and vulnerability under pressure), and to examine whether the task and social intra-group conflict act as mediators between commitment to the team and team resilience factors. One hundred seventy (170) male soccer players (16-38 years; M = 18.35; SD = 4.72) of the national teams of Argentina, Costa Rica, and Mexico participated in the study. The path analytic model was used to test mediating pathways. First, the results revealed that commitment to the team was positively related to characteristics of resilience and negatively to vulnerability under pressure. Second, bootstrap mediation analysis showed that athletes` perceptions of the task and social intra-group conflict mediated the association between their perception of commitment to the team and team resilience factors. Findings provide initial evidence for a link between commitment to the team and team resilience in national teams and also suggest that intra-group conflict can improve the association between commitment to the team and team resilience. Therefore, the main conclusion of this study is that practioners should promote players` commitment to the team and avoid intra-group conflicts within teams to have a resilient team that copes with problems more easily.